Prevention of sinonasal inflammation by a synthetic glycosaminoglycan. Issue 2 (11th November 2016) - Pulsipher, Abigail; Qin, Xuan; Thomas, Andrew J.; Prestwich, Glenn D.; Oottamasathien, Siam; Alt, Jeremiah A.
Abstract : Background: Glycosaminoglycans (GAGs) are polysaccharides that are distributed on respiratory epithelial cells, endothelial cells, and submucosal glands. Uniquely positioned, certain GAGs exhibit anti‐inflammatory properties in respiratory diseases and serve important roles in repairing mucosal surfaces and modulating mucociliary clearance. We hypothesized that topical administration of a synthetic GAG (GM‐0111) would prevent sinonasal inflammation in a mouse model of rhinosinusitis (RS). Methods: To test our hypothesis, C57BL/6 mice were intranasally administered fluorescent GM‐0111, and sinonasal tissues were examined for coating and penetration ability. To test therapeutic feasibility, mice (n = 6) were given GM‐0111 or hyaluronic acid (HA; 800 μg dose) prior to inducing RS with inflammatory molecule LL‐37 (115 μg dose). After 24 hours, sinonasal tissues were harvested for histological and biochemical analysis of inflammatory markers (inflammatory cell infiltration, lamina propria [LP] thickening, and neutrophil enzyme myeloperoxidase [MPO]) and cell death. Results: GM‐0111 was observed within sinonasal tissues 1 hour and 24 hours after intranasal administration, indicating rapid and effective coating and penetration. GM‐0111 prevented sinonasal tissues from developing inflammatory changes, with significant reductions in mast cell infiltration ( p < 0.05), LP thickening ( p < 0.001), and MPO levels ( p < 0.01) when compared to tissues treated with LL‐37 and those pretreated with HA. GM‐0111 reduced cell death within sinonasal tissues in contrast to LL‐37–treated tissues. Conclusion: We report a new synthetic GAG (GM‐0111) that uniformly coats and penetrates into the sinonasal mucosa to prevent sinonasal inflammation and cell death in a mouse model of RS.